Antibacterial Therapeutic Agents Composed of Functional Biological Molecules - Dawei Li; Bing Zhou; Bei Lv (Journal of Chemistry)
Antibacterial agents are a group of materials that selectively destroy bacteria by interfering with bacterial growth or survival. With the emergence of resistance phenomenon of bacterial pathogens to current antibiotics, new drugs are frequently entering into the market along with the existing drugs, and the alternative compounds with antibacterial functions are being explored. Due to the advantages of their inherent biochemical and biophysical properties including precise targeting ability, biocompatibility, biodegradability, long blood circulation time, and low cytotoxicity, biomolecules such as peptides, carbohydrates, and nucleic acids have huge potential for the antimicrobial application and have been extensively studied in recent years. In this review, antimicrobial therapeutic agents composed of three kinds of functional biological molecules were summarized. In addition, the research progress of antibacterial mechanism, chemical modification, and nanoparticle coupling of those biomolecules were also discussed.